Midgut Bacterial Communities of Vespa velutina Lepeletier (Hymenoptera: Vespidae) - Zhang, Li; Liu, Feng; Wang, Xin-Ling; Wang, Pin-Hong; Ma, Shi-Long; Yang, Yang; Ye, Wu-Guang; Diao, Qing-Yun; Dai, Ping-Li (Frontiers in Ecology and Evolution, 2022)
Vespa velutina nigrithorax and Vespa velutina auraria are two subspecies of Vespa velutina Lepeletier. V. velutina preys managed honey bees, other pollinators and insects. While the Vespa midgut microbiota of three forms queens, workers, and males has not been reported, thus the objective of this study was to analyze midgut bacterial diversity of three forms queens, workers, and males of V. v. nigrithorax and V. v. auraria. Our results showed that Proteobacteria, Firmicutes, Bacteroidetes, Tenericutes, and Actinobacteria were the most abundant phyla, and Lactobacillus (17.21%) and Sphingomonas (11.39%) were the most abundant genera in the midgut of V. v. nigrithorax and V. v. auraria. We found that the midgut bacterial compositions of the V. velutina males were special, in terms of richness and diversity of bacterial communities, as well as the content of lactic acid bacteria. By comparing the gut bacterial compositions of Vespa from different regions (Japan, Korea, Italy and China), it was discovered that the gut bacterial compositions were very similar at the phylum and class level, and Gammaproteobacteria, Bacilli and Alphaproteobacteria were the most abundant classes of bacteria and consistent in the genus Vespa. Besides, though Vespa from different regions had quite different gut bacterial communities in the genus level, Lactobacillus and other lactic acid bacteria were abundant and played important roles in protection and metabolism in V. velutina collected from different regions. This is the first report of midgut bacterial diversity of three forms queens, workers, and males of V. velutina. Our findings provide insight that Proteobacteria and Firmicutes (especially Lactobacillus and other lactic acid bacteria) are consistent and may play important roles in the genus Vespa. Understanding of the microbiome in the midgut of Vespa and discovery of the vital bacteria would provide useful information to design pest biological control agents. Thus the significance of this study is to provide a basis for the study of the relationship between gut microbiota and physiology and health of Vespa, as well as the control of Vespa.